(untitled) (Papeles, 2024)
Introduction: University education must respond to social demands and offer students comprehensive training that goes beyond the acquisition of knowledge. The objective of this research is to delve into the convenience of using the dramatic technique called role-plays so that students acquire social skills and delve into the principles of global citizenship education (GCE) while developing oral skills in English. The research question is the following: Is role-plays an appropriate dramatic technique for students to develop their oral skills while advancing as global citizens? Methodology: The methodology is quantitative since it offers, on the one hand, the results of a rubric completed by the students and the teacher in her role as researcher during the teaching-learning process, and on the other hand, the results of a questionnaire in Google Forms that the students completed at the end of the semester. Results and discussion: The findings show that the students are aware that by participating in role-plays they not only develop oral skills, but also acquire social competences such as communication or cooperation. In addition, the fact that global topics are used in the role-plays allows to deepen the principles of the GCE. Conclusion: In conclusion, it should be noted that working with socially themed role-plays contributes to humanizing teaching and offering students a context in which to reflect on global issues that challenge society.